Respon Pertumbuhan dan Karakteristik Miselia F3 Isolat FP007 Jamur Merang (Volvariella volvaceae) FAPERTA UNSIKA Pada Media yang Berbeda secara In Vitro. - Apriliahetty, Laila Ais; Afifah, Lutfi; Samaullah, Mohammad Yamin; Lestari, Ani (UNIVERSITAS LABUHANBATU, 2023)
Straw mushroom (Volvariella volvaceae) is a horticultural product and one of the many tropical and subtropical mushroom species known and in demand by the people of Indonesia. Currently the growth of straw mushroom is still low, this is because the quality seeds are not sufficient and the price is relatively expensive. Quality seeds are not only determined from superior mushroom broodstock, but also determined by the quality of the pure culture, the production of pure culture is constrained by the type of material for making in vitro media. The purpose of this study was to obtain the type of in vitro media that gave the highest growth response and features of the F3 mycelial isolate FP007 mushroom Faperta Unsika. The research method used was by using a single factor Complete Randomized Design (CRD), there were 5 replications and 7 treatments consisting of: 100% PDA (A), 100% Charcoal Husk (B), 100% Husk (C), 80 PDA % + Husk 20% (D), PDA 80% + Charcoal Husk 20% (E), PDA 60% + Husk 20% + Charcoal Husk 20% (F), and Husk 50% + Charcoal Husk 50%. The results of this study showed that 80% PDA media + 20% rice husk charcoal had the highest effect on the growth response and characteristics of the F3 mycelia isolate FP007 straw mushroom Faperta Unsika with a mushroom mycelia growth diameter of 7 cm. Rice husk charcoal media can be used as a good additive for the manufacture of growing media in vitro. Keywords : Charcoal husk, rice husk, pure culture, straw mushroom.